Real-Time Scene Monitoring for Deaf-Blind People - Khaled Kassem; Piergiorgio Caramazza; Kevin J. Mitchell; Mitch Miller; Azadeh Emadi; Daniele Faccio (Sensors, 2022)
It is estimated that at least 15 million people worldwide live with severe deaf-blindness, with many more experiencing varying degrees of deaf-blindness. The existing options of assistance are mostly limited to walking canes, guide dogs and human care. We propose a wearable device which harnesses a multi-antenna mmWave radar transceiver and a haptic feedback array for real time detection of a person moving within a scene. We present our findings from a series of workshops with participants classed with multi-sensory impairments (MSI), to demonstrate the relative success of this approach and its potential for integration into existing assistance for the MSI of the future.